Conceptualization Good Amil Governance In Zakat Institution - Fitri Laela Wijayati (Profesional Muda Cendekia Publishing, 2021)
This study aims to analyze the implementation of good amil governance in the largest zakat organization in Indonesia to provide an overview of the extent of the implementation of good amil governance. OPZ performance is not only measured by the effectiveness of zakat distribution but also seen from professionalism in organizational management which is reflected in the creation of good organizational governance Professional management is an effort to create new public management and increase public trust in OPZ. Public trust in OPZ is very important because it relates to trust in the management and distribution of zakat in a professional manner which in turn can increase the potential for zakat acceptance so that it can be used to improve social welfare. This research is a qualitative study by analyzing the contents of the financial statements and websites of zakat organizations. The implementation of Good Governance (GG) is an important issue in order to improve the performance of OPZ which can be seen from the aspects of management, public services and public trust (muzakki) in the organization The implementation of GG in public organizations is inseparable from the principles of transparency, accountability, responsibility, independence, and openness / honesty which are in line with the norms and ethics principles in Islamic Sharia. The results show that most zakat organizations have implemented good amil governance, but there are some components that have not been disclosed in the financial statements or websites.